TECHNOLOGIES FOR ELIMINATING THE SHORTCOMINGS IN THE PRONUNCIATION OF SOUNDS OF PRIMARY SCHOOL STUDENTS - Makhmudova Madinakhan Sobirkhanovna; Toshmatova Zumradkhan (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the child with normal speech development, the technologies for eliminating the deficits in the pronunciation of sounds of elementary school students pronounce all the sounds in speech, use words in their place, logically correct statement of their opinion the periods of speech formation of children with defects in speech, sound pronunciation and articulation are described.